Taâ€™thÄ«r IstikhdÄm WasÄ«lah al-Qiá¹£á¹£ah al-MuqÄá¹aÊ¿ah fÄ« Taá¸¥sÄ«n MahÄrah al- QirÄâ€™ah - Putri, Yosi Yunia; Hasnah, Nur (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2023)
The problem in this study is the lack of activity in the reading Arabic texts among the students, wich leads to the decrease in the interest and enthusiasm for the learning the Arabic language. One of the teaching media that make it easier for students to fill the lessons so that they can achieve excellent results is the strip story. In addition to the interesting media, how to make it is also easy and does not require a lot of money. This media can be used as training in reading using illustrated text. The method used in this study is experimental method with True Experimental Design; Postest-Only Control Design, giving R (random) consisting of two design. The method of data collection, it is observation and tests and use of research analysis using the T-test rule. The writer founfd result ofÂ  T computer is 3,098 and T table is 1,701, so the result it of the computational is greater than the tables T .The writer reached the conclusion that the use of the interrupted story method in the nine class in Alzamriyah islamic boarding School Simalanggang Payakumbuh in other words, the extent of influence on students reading skill is 20%.Â ÙˆØ§Ù„Ù…Ø´ÙƒÙ„Ø© ÙÙŠ Ù‡Ø°Ù‡ Ø§Ù„Ø¯Ø§Ø±Ø³Ø© Ù‚Ù„Ø© Ø§Ù„Ù†Ø´Ø· ÙÙŠ Ù‚Ø±Ø§Ø¡Ø© Ø§Ù„Ù†ØµÙˆØµ Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø¯Ù‰ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ°ØŒ Ù…Ù…Ø§ ÙŠØ¤Ø¯ÙŠ Ø¥Ù„Ù‰ Ø§Ù†Ø®ÙØ§Ø¶ Ø§Ù„Ø¥Ù‡ØªÙ…Ø§Ù… ÙˆØ§Ù„ØÙ…Ø§Ø³ Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ‚Ù„Ø© Ø§Ù„Ø±ØºØ¨Ø© Ù„ØªØ¹Ù„Ù… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©. Ø¥ØØ¯Ù‰ ÙˆØ³Ø§Ø¦Ù„ Ø§Ù„ØªØ¹Ù„ÙŠÙ…ÙŠØ© Ø§Ù„ØªÙŠ ØªØ³Ù‡Ù„ Ø¹Ù„Ù‰ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° ÙØ¹Ù… Ø§Ù„Ø¯Ø±ÙˆØ³ ØØªÙ‰ ÙŠØªÙ…ÙƒÙ†ÙˆØ§ Ù…Ù† ØªØÙ‚ÙŠÙ‚ Ù†ØªØ§Ø¦Ø¬ Ù…Ù…ØªØ§Ø±Ø© Ù‡ÙŠ ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ù‚ØµØ© Ø§Ù„Ù…Ù‚Ø§Ø·Ø¹Ø©. Ø¨Ø§Ù„Ø¥Ø¶Ø§ÙØ© Ø¥Ù„Ù‰ Ø§Ù„ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ù…Ø«ÙŠØ±Ø© Ù„Ù„Ø§Ù‡ØªÙ…Ø§Ù…ØŒ ÙØ¥Ù† ÙƒÙŠÙÙŠØ© Ø¬Ø¹Ù„Ù‡Ø§ Ø³Ù‡Ù„Ø© Ø£ÙŠØ¶Ù‹Ø§ ÙˆÙ„Ø§ ØªØªØ·Ù„Ø¨ Ø§Ù„ÙƒØ«ÙŠØ± Ù…Ù† Ø§Ù„Ù…Ø§Ù„. ÙˆÙ‡Ø°Ù‡ Ø§Ù„ÙˆØ³ÙŠÙ„Ø© ÙŠÙ…ÙƒÙ† Ø§Ø³ØªØ®Ø¯Ø§Ù…Ù‡Ø§ ÙƒØ§Ù„ØªØ¯Ø±ÙŠØ¨ Ø¹Ù„Ù‰ Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ù†Øµ Ø§Ù„Ù…ØµÙˆØ±. Ù†ÙˆØ¹ Ø§Ù„Ø¨ØØ« Ù‡Ùˆ Ø§Ù„Ø¨ØØ« Ø§Ù„ÙƒÙ…ÙŠ Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù… Ø§Ù„Ø·Ø±ÙŠÙ‚Ø© Ø§Ù„ØªØ¬Ø±ÙŠØ¨ÙŠØ©. ÙÙŠ Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ø³ØªØ¹Ù…Ù„Øª Ø§Ù„ÙƒØ§ØªØ¨Ø© ØªØµÙ…ÙŠÙ… Ø¨Ù†ÙˆØ¹ True Â Eksperimental DesignØŒ Posttest-Only Control DesignØŒ ØªØ¹Ø·ÙŠ Random Â ((RÂ  ÙŠØªÙƒÙˆÙ† Ù…Ù† Ø§Ù„ØªØµÙ…ÙŠÙ…ÙŠÙ†. ÙˆØ£Ù…Ø§ Ø£Ø³Ù„ÙˆØ¨ Ø¬Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª ÙÙ‡ÙŠ Ø§Ù„Ù…Ù„Ø§ØØ¸Ø© ÙˆØ§Ù„Ø§Ø®ØªØ¨Ø§Ø±Ø§Øª. ÙˆØ§Ø³ØªØ¹Ù…Ø§Ù„ ØªØÙ„ÙŠÙ„ Ø§Ù„Ø¨ØØ« Ù‚Ø§Ø¹Ø¯Ø© Ø§Ø®ØªØ¨Ø§Ø± "Øª" . ÙˆØ¬Ø¯Øª Ø§Ù„ÙƒØ§ØªØ¨Ø© Ø£Ù† Ù†ØªÙŠØ¬Ø© ØªØ§Ø¡ Ø§Ù„ØØ³ÙˆØ¨ (3ØŒ098) ÙˆØªØ§Ø¡ Ø§Ù„Ø¬Ø¯ÙˆÙ„ (1ØŒ701) ÙÙ†ØªÙŠØ¬Ø© ØªØ§Ø¡ Ø§Ù„ØØ³Ø§Ø¨ Ø£ÙƒØ¨Ø± Ù…Ù† ØªØ§Ø¡ Ø§Ù„Ø¬Ø¯ÙˆÙ„. ÙˆØªÙˆØµÙ„Øª Ø§Ù„Ø¨Ø§ØØ«Ø© Ø¥Ù„Ù‰ Ø§Ù„Ø®Ù„Ø§ØµØ© Ø£Ù† Ø§Ø³ØªØ®Ø¯Ø§Ù… ÙˆØ³ÙŠÙ„Ø© Ø§Ù„Ù‚ØµØ© Ø§Ù„Ù…Ù‚Ø§Ø·Ø¹Ø© ÙÙŠ Ø§Ù„ÙØµÙ„ Ø§Ù„ØªØ§Ø³Ø¹Â  ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø©Â  Ø§Ù„Ø²Ù…Ø±ÙŠØ© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¯Ø§Ø®Ù„ÙŠØ© Ø³ÙŠÙ…Ø§Ù„Ø§Ù†Ø¬Ù†Ø¬ Ø¨Ø§ÙŠØ§ÙƒÙ…Ø¨ÙˆÙ‡ Ø¨Ø§Ù„Ù…Ø¹Ù†Ù‰ Ø§Ù„Ø¢Ø®Ø±ØŒ Ù…Ø¯Ù‰ ØªØ£Ø«ÙŠØ± Ù‚ÙˆÙŠÙ‘Ø§ Ø¹Ù„Ù‰ ØªØ±ÙƒÙŠØ© Ù…Ù‡Ø§Ø±Ø© Ø§Ù„Ù‚Ø±Ø§Ø¡Ø© Ø¹Ù†Ø¯ Ø§Ù„ØªÙ„Ø§Ù…ÙŠØ° Ù‡Ùˆ 20% .